Strategi Manajemen Pelanggan Internet Rumah Pascabayar Berdasarkan Faktor yang Berpengaruh Terhadap Churn - Didik Prianto (Inovbiz: Jurnal Inovasi Bisnis, 2020)
In the era of connectivity, the internet industry has significantly increased year by year. The annual compound growth rate (CAGR) of Indonesian internet users is about 21.8% (2007-2017). The penetration rate of Indonesian internet users is about 54.7%, making this industry will be growing up. However, the competition of the internet industry is very high and the company facing the churn of the customer problem. This study aims to analyze the factors that affected customers churn. The result of logistic regression shows that the experience of service blocking, ownership of the residence, changing internet speed, city of residence, monthly internet fee, registration method, gerai payment method, socioeconomic class of residence, age of the customer, telephony service, and gender of customer has significantly affected to customer churn. The findings should be considered by the company to develop a customer management strategy. To acquire new customer, the company need to consider male, age above 35 y.o, medium-high SEC of residence and self-owned residence as a target market. To prevent customer churn, company need to revamp customer experience on service blocking and offering upgrade or downgrade internet speed according to customer needs.